2019
DOI: 10.1021/acs.jpcc.8b11575
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Transport via Optical Heating of a Single Gold Nanoparticle

Abstract: Optothermal trapping has gained increasing popularity in manipulation such as selecting, guiding, and positioning submicron objects because of a few mW laser power much lower than that required for optical trapping. Optothermal trapping uses thermal-gradient-induced phoretic motions, but the underlying physics of driving force has not been fully understood. In this study, we performed optothermal trapping of 500 nm-diameter colloidal silica via a continuous laser illumination of a single gold nanoparticle from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The speed of the tracer NP and its increase in the proximity of the G-NP, as well as the tracer trajectory always pointing towards the hot G-NP, support our hypothesis. Note that the thermophoretic force cannot explain the observed motion of tracers towards the heat source since its direction in the considered water solution should be from the hot to cold region (positive Soret coefficient) 29 . We have observed that the trajectories followed by the tracers initially located at the same distance from the heat source (~6 μm) have different shapes depending on the constant or variable speed of the G-NP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The speed of the tracer NP and its increase in the proximity of the G-NP, as well as the tracer trajectory always pointing towards the hot G-NP, support our hypothesis. Note that the thermophoretic force cannot explain the observed motion of tracers towards the heat source since its direction in the considered water solution should be from the hot to cold region (positive Soret coefficient) 29 . We have observed that the trajectories followed by the tracers initially located at the same distance from the heat source (~6 μm) have different shapes depending on the constant or variable speed of the G-NP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the high temperature of the G-NP and therefore of the surrounding medium can produce different optofluidics effects. Taking into account the experimental conditions (trapping near the ceiling substrate) and the estimated temperature of the G-NP (~500 K) and following the reasoning as well as simulation results of a recent work 29 (where the optothermal flows generated by a single 100 nm gold NP fixed on a ceiling substrate were considered), we suppose that the flow originates from the temperature-induced Marangoni effect at the liquid water/superheated water interface due to nanobubble formation. The speed of the tracer NP and its increase in the proximity of the G-NP, as well as the tracer trajectory always pointing towards the hot G-NP, support our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations